Diagnostic Performance of a Staged Pathway for Imaging Acute Appendicitis in Children. Issue 12 (December 2021) - Ahmad, Tahani; Khdair Ahmad, Fareed; Manson, David
Abstract : Introduction: The objective of this work is to assess the performance of our staged diagnostic pathway in the evaluation of suspected appendicitis cases in children. The pathway consisted of clinical assessment by the emergency physician, performing initial ultrasound (US), consultation, and clinical reevaluation by the surgery team followed by a repeat focused US scan in inconclusive cases. Computed tomography (CT) was limited to cases where the repeat US remained inconclusive and the clinical reassessment indicated persistent concerns for appendicitis. Method: Retrospective review of the electronic medical records of 206 consecutive children who presented to our emergency department with acute abdominal pain and underwent US examination for suspected appendicitis. The imaging findings, management plan, and surgical outcome (in those who underwent surgery) were reviewed. The diagnostic performance of the initial US, repeat US, and the full imaging protocol were evaluated including the negative appendectomy rate (NAR) and the number of CT scans performed. Results: Of the 206 cases, 73 (35.4%) had appendicitis. Computed tomography was performed in 9 (4.3%) of 206 cases. The US/CT ratio was 23:1. Our approach showed a diagnostic accuracy of 95.6% (197/206), sensitivity of 97.3% (73/75), specificity of 93.7% (124/133), positive predictive value of 89.0% (73/82), and negative predictive value of 98.7% (82/95). The NAR was 2.7% (2/72). The accuracy of the protocol is higher than that of the initial US alone (61.2%; 126/206) and that of the repeat US (84.2%; 16/19). Conclusion: The strategy of repeating limited focused US followed by CT scan in cases that remain inconclusive has good diagnostic accuracy and reasonable NAR and decreases the number of CT scans.